Effect of stent crimping on calcification of transcatheter aortic valves. (21st February 2019) - Zareian, Ramin; Tseng, Jen-Chieh; Fraser, Robert; Meganck, Jeffrey; Kilduff, Marshall; Sarraf, Mohammad; Dvir, Danny; Kheradvar, Arash
Abstract: OBJECTIVES: Although many challenges related to the acute implantation of transcatheter aortic valves have been resolved, durability and early degeneration are currently the main concerns. Recent reports indicate the potential for early valve degeneration and calcification. However, only little is known about the underlying mechanisms behind the early degeneration of these valves. The goal of this study was to test whether stent crimping increases the risk for early calcification. METHODS: Stented valves that were crimped at 18-Fr and 14-Fr catheter and uncrimped controls were exposed to a standard calcifying solution for 50 million cycles in an accelerated wear test system. Subsequently, the leaflets of the valves were imaged by microcomputed tomography (micro-CT) followed by histochemical staining and microscopic analyses to quantify calcification and other changes in the leaflets' characteristics. RESULTS: Heavily calcified regions were found over the stent-crimped leaflets compared to uncrimped controls, particularly around the stent's struts. Micro-CT studies measured the total volume of calcification in the uncrimped valves as 77.31 ± 1.63 mm 3 vs 95.32 ± 5.20 mm 3 in 18-Fr and 110.01 ± 8.33 mm 3 in 14-Fr stent-crimped valves, respectively. These results were congruent with the increase in leaflet thickness measured by CT scans (0.44 ± 0.07 mm in uncrimped valves vs 0.69 ± 0.15 mm and 0.75 ± 0.09 mm in 18-Fr and 14-Fr stent-crimped valves, respectively). Histological studies confirmed the micro-CT results, denoting that the percentage of calcification in uncrimped leaflets at the valve's posts was 5.34 ± 3.97 compared to 19.97 ± 6.18 and 27.64 ± 13.17 in the 18-Fr and 14-Fr stent-crimped leaflets, respectively. CONCLUSIONS: This study concludes that stent-crimping damage is associated with a higher level of passive leaflet calcification, which may contribute to early valve degeneration.